RESPON BEBERAPA VARIETAS WIJEN (Sesamum indicum L.) DENGAN JAGUNG (Zea mays) TERHADAP SISTEM TUMPANGSARI - , YASON EDISSON BENU ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The experiment was conducted in the Universitas Gadjah Mada Experimental and Development Garden (KP4) in Kalitirto Berbah, Sleman, from September to December 2001. The objective of the study was to find out the combination of sesame varieties which is suitable for intercropping with maize. A strip plot design was used with three replications. The factorial treatment consisted of two factors. The first factor was sesame varieties (Sumberrejo 1 and Sumberrejo 2). The second factor was maize varieties (Hibrida and Lamuru). In each replication, sesame and maize varieties were planted as monocultures. The plot size was 4 m x 6 m, sesame and maize plant spacing were 0,50 m x 0,25 (Sumberrejo 1), 0,45 m x 0,20 m (Sumberrejo 2) and 1,0 m x 0,20 m (Hibrida and Lamuru) respectively. The results showed that the intercropping of sesame Sumbererjo 1 variety and maize Hibrida variety produced 409,98 kg/ha sesame seed per plot and 7544,00 kg/ha seed maize per plot. The highest relative total yield on intercropping sesame and maize was obtained by Sumberrejo 2 and Lamuru at 1,26 and the lowest relative total yield was obtained by Sumberrejo 2 and Hibrida at 1,32. RYT value of the intercropping system was more than one which is considered as efficient in land use.